In-Out Surface Modification of Halloysite Nanotubes (HNTs) for Excellent Cure of Epoxy: Chemistry and Kinetics Modeling - Shahab Moghari; Seyed Hassan Jafari; Mohsen Khodadadi Yazdi; Maryam Jouyandeh; Aleksander Hejna; Payam Zarrintaj; Mohammad Reza Saeb (Nanomaterials, 2021)
In-out surface modification of halloysite nanotubes (HNTs) has been successfully performed by taking advantage of 8-hydroxyquinolines in the lumen of HNTs and precisely synthesized aniline oligomers (AO) of different lengths (tri- and pentamer) anchored on the external surface of the HNTs. Several analyses, including FTIR, H-NMR, TGA, UV-visible spectroscopy, and SEM, were used to establish the nature of the HNTs’ surface engineering. Nanoparticles were incorporated into epoxy resin at 0.1 wt.% loading for investigation of the contribution of surface chemistry to epoxy cure behavior and kinetics. Nonisothermal differential scanning calorimetry (DSC) data were fed into home-written MATLAB codes, and isoconversional approaches were used to determine the apparent activation energy (Eα) as a function of the extent of cure reaction (α). Compared to pristine HNTs, AO-HNTs facilitated the densification of an epoxy network. Pentamer AO-HNTs with longer arms promoted an Excellent cure; with an Eα value that was 14% lower in the presence of this additive than for neat epoxy, demonstrating an enhanced cross-linking. The model also predicted a triplet of cure (m, n, and ln A) for autocatalytic reaction order, non-catalytic reaction order, and pre-exponential factor, respectively, by the Arrhenius equation. The enhanced autocatalytic reaction in AO-HNTs/epoxy was reflected in a significant rise in the value of m, from 0.11 to 0.28. Kinetic models reliably predict the cure footprint suggested by DSC measurements.